Consumption of bladder irritant liquids and foods by incontinent women - Guedes, Priscilla Fonseca; Santana, Samira Félix; Colpo, Elisângela (Disciplinarum Scientia | Saúde, 2019)
Excessive fluid intake has a significant impact on lower urinary tract symptoms, and studies have lately questioned whether the amount of caffeine-based beverages ingested as well as acidic foods worsen symptoms of UI. A bibliographic review of national and international literature was carried out. The scientific articles selected were published in the last ten years, until October 2017, indexed in the databases of Scielo, Pubmed and Lilacs. The descriptors were: female urinary incontinence, urinary incontinence symptoms and food, which were typed associated with each other. Through the selection, only 11 articles presented the inclusion criteria. It was therefore possible to observe that moderate consumption of citrus fruits and caffeinated liquids does not worsen the symptoms of urinary incontinence and is not considered a primary factor to develop incontinence. However, further studies for a better understanding of this association are suggested, as well as for more precise guidelines on the prevention of urinary incontinence.